2021
DOI: 10.1097/bot.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Fractures of the Distal Tibial Articular Surface in Tibia Shaft Fractures: Is Computed Tomography Always Necessary?

Abstract: Objectives: To identify the incidence of distal articular fractures in a series of distal third tibia shaft fractures and to report the utility of both computed tomography (CT) scans and Radiographic Investigation of the Distal Extension of Fractures into the Articular Surface of the Tibia (RIDEFAST) ratios for identification of articular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…This is consistent with other recent literature reports that show that the prevalence of clinically significant fractures is high but can be frequently detected on plain x-ray alone. 14 There are several limitations to this study. Although we have x-rays at time of union in most patients (74% of patients with at least 3-month follow-up and 55% of patients with 6-month follow-up), the retrospective nature of this study means that we do not have patient-reported outcomes, making us unable to definitively evaluate the clinical impact of these injuries.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This is consistent with other recent literature reports that show that the prevalence of clinically significant fractures is high but can be frequently detected on plain x-ray alone. 14 There are several limitations to this study. Although we have x-rays at time of union in most patients (74% of patients with at least 3-month follow-up and 55% of patients with 6-month follow-up), the retrospective nature of this study means that we do not have patient-reported outcomes, making us unable to definitively evaluate the clinical impact of these injuries.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with other recent literature reports that show that the prevalence of clinically significant fractures is high but can be frequently detected on plain x-ray alone. 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, the utilization of advanced imaging has escalated 21-23 . Modern day CT scanning machines are readily available and efficient, and new trainees are in the habit of obtaining scans on many injuries.…”
Section: Discussionmentioning
confidence: 99%